STAND PAMERAN PROKLIM RW-11 PEKAYON JAYA SEBAGAI SARANA PENINGKATAN KUALITAS EDUKASI DAN MARKETING KAMPANYE LINGKUNGAN - Samsu Hendra Siwi (Jurnal Bakti Masyarakat Indonesia, 2026)
Public awareness of the dangers and impacts of climate change affecting the world (globally) and the residential environment (locally) will affect all aspects of life. Adaptation and mitigation programs for climate change serve as the background for activities in the RW 11 Pekayon Jaya community, South Bekasi. The PROKLIM program (Climate Village Program) is a community-based initiative at the “RT and RW” levels across Indonesia that involves communities, private institutions, government institutions, and other stakeholders. This program needs to be continuously socialized to the community. One of the socializations carried out is the holding of an environmental exhibition. The fact is that not all residents are involved or aware of RW 11's PROKLIM activities. Community participation must still be increased through educational activities and exhibitions at events held in the RW 11 environment. The commemoration of August 17 as Indonesian Independence Day, which involves all residents, is an important occasion to gather residents and showcase PROKLIM RW 11's activities, which have achieved notable results at the national level. Participation in the exhibition at the 17 August commemoration bazaar is crucial to attracting residents to achieve environmental quality improvement activities. The PKM implementation method is to provide assistance in the construction of the PROKLIM RW 11 exhibition stand. The result of this PKM is the PROKLIM RW 11 exhibition stand for the Republic of Indonesia Independence Day Commemoration event.